Quaternary deserts and climatic change : proceedings of the International Conference on Quaternary Deserts and Climatic Change, Al Ain, United Arab Emirates, 9-11 December 1995 /: proceedings of the International Conference on Quaternary Deserts and Climatic Change, Al Ain, United Arab Emirates, 9-11 December 1995. (2020) - Unknown
No abstract available